A Versatile Electrochemical Biosensor for the Detection of Circulating MicroRNA toward Non‐Small Cell Lung Cancer Diagnosis (Small 22/2022). Issue 22 (2nd June 2022) - Meng, Fanyu; Yu, Wenjun; Chen, Changqiang; Guo, Susu; Tian, Xiaoting; Miao, Yayou; Ma, Lifang; Zhang, Xiao; Yu, Yongchun; Huang, Lin; Qian, Kun; Wang, Jiayi
Abstract : Cancer Diagnostics In article number 2200784, Kun Qian, Jiayi Wang, and co‐workers develop a versatile electrochemical biosensing system for circulating miRNA detection by DNAzyme cleavage cycling amplification and hybridization chain reaction amplification. By profiling miRNA in a non‐small‐cell lung cancer cohort, this designed liquid biopsy strategy shows high efficiency and sensitivity for early diagnosis and prognosis toward clinical use.